Some critical aspects in the application of the corporative tax to cooperatives according to the tax regime to cooperatives. Its necessary reform - Agustín Romero Civera (AECOOP Escuela de Estudios Cooperativos, 2015)
This paper aims to highlight the difficulties that cooperatives have in the calculation of corporate tax as a consequence of the application of the tax regime of cooperatives. There are some specific questions which affect corporate tax calculation: a) the existence of different types of results, affected by different tax rates; b) the endowment to some obligatory social funds, totally or partially deductible, the calculation of which can be made before or after taxes; c) the discrepancies in the qualification of different items by the substantive law and the tax law imply some problems in practical application or, sometimes, impossible solutions to comply with both substantive legislation and tax legislation. This situation implies a clear disadvantage when compared with other types of societies which are far less complex. As a result, we propose some solutions, such as: a) the existence of only one type of result, with only one tax rate; b) the exclusive taxation of the non-cooperative profit, resulting in tax exemption on cooperative profit, given that partners of the cooperative will pay it in their income tax later; c) maintaining both types of results with both tax rates but eliminating the discrepancies between the substantive law and the tax law, as well as allowing adjustments only to the cooperative result.